2012
DOI: 10.1007/s13105-012-0164-0
|View full text |Cite
|
Sign up to set email alerts
|

Light aerobic physical exercise in combination with leucine and/or glutamine-rich diet can improve the body composition and muscle protein metabolism in young tumor-bearing rats

Abstract: Nutritional supplementation with some amino acids may influence host's responses and also certain mechanism involved in tumor progression. It is known that exercise influences body weight and muscle composition. Previous findings from our group have shown that leucine has beneficial effects on protein composition in cachectic rat model as the Walker 256 tumor. The main purpose of this study was to analyze the effects of light exercise and leucine and/or glutamine-rich diet in body composition and skeletal musc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 36 publications
1
27
0
4
Order By: Relevance
“…Our previous work showed some important impairments in skeletal muscle in tumour‐bearing rats, which had increased chymotrypsin activity, representing enhancements of the ubiquitin–proteasome pathway . The present results likely suggest that the higher proteolytic activity (increased chymotrypsin activity) that is associated with higher cell activity (higher AP activity) in heart tissue could be responsible for the ECG failure that was observed only in group W. In our previous research, as also found here, the leucine‐rich diet also minimized the observed changes in those enzymes, even in the heart. Despite the presence of tumour, the LW group exhibited some improvements in cardiac tissue, with minimal damaging effects produced by tumour development, as confirmed by the significant diet interaction effect.…”
Section: Discussionsupporting
confidence: 82%
“…Our previous work showed some important impairments in skeletal muscle in tumour‐bearing rats, which had increased chymotrypsin activity, representing enhancements of the ubiquitin–proteasome pathway . The present results likely suggest that the higher proteolytic activity (increased chymotrypsin activity) that is associated with higher cell activity (higher AP activity) in heart tissue could be responsible for the ECG failure that was observed only in group W. In our previous research, as also found here, the leucine‐rich diet also minimized the observed changes in those enzymes, even in the heart. Despite the presence of tumour, the LW group exhibited some improvements in cardiac tissue, with minimal damaging effects produced by tumour development, as confirmed by the significant diet interaction effect.…”
Section: Discussionsupporting
confidence: 82%
“…In our previous data, the tyrosine content was inversely proportional to the tyrosine release, indicating protein degradation [23,27,32]. Conversely, all of the leucine groups had decreased tyrosine contents when compared to the control group, although no difference was found among the leucine groups (Table 1).…”
Section: Mac16 Tumor Growth and Leucine Supplementation Increase Pc5 mentioning
confidence: 67%
“…The normoprotein control diet consisted of 18% protein (casein was the sole source of protein, which contained 1.6% Lleucine). The leucine-rich diet contained 18% protein and an additional 3% Lleucine [32] (for humans, this dosage corresponds to an intake of ;2 g leucine per day). Both diets contained similar amounts of nitrogen (;13.2 mg N 2 /100 g diet).…”
Section: Animalsmentioning
confidence: 99%
See 1 more Smart Citation
“…The diets were supplemented with a mixture of vitamins, minerals, cysteine and choline. The control diet contained 1.6% L-leucine, and the leucine-rich diet contained 4.6% L-leucine; these diets were identical to those used in our previous experimental studies [5,24-26]. …”
Section: Methodsmentioning
confidence: 99%